رؤية مستقبلية لتطوير التعليم الفني والمهني في مصر في ضوء خبرتي كندا والولايات المتحدة الأمريكية - الرشيدي، هشام حسنين محمد علي (الجمعية المصرية للتربية المقارنة والإدارة التعليمية, 2016)
تسعى هذه الدراسة إلى تحقيق أهدافها من خلال طرح مجموعة من الأسئلة والإجابة عنها، وفي ضوء ذلك يمكن صياغة مشكلة البحث في الأسئلة التالية: السؤال الرئيسي: كيف يمكن تطوير التعليم الفني والمهني في مصر في ضوء الاستفادة من خبرتي كندا والولايات المتحدة الأمريكية؟ ويتفرع من هذا السؤال الرئيس الأسئلة الفرعية الآتية: 1. ما الاتجاهات العالمية المعاصرة لتطوير التعليم الفني والمهني؟ 2. ما واقع التعليم الفني والمهني في مصر في ضوء القوى والعوامل الثقافية المؤثرة فيها؟ 3. ما واقع التعليم الفني والمهني في كندا في ضوء القوى والعوامل الثقافية المؤثرة فيها؟ 4. ما واقع التعليم الفني والمهني في الولايات المتحدة الأمريكية في ضوء القوى والعوامل الثقافية المؤثرة فيها؟ 5. ما التحليل المقارن لواقع التعليم الفني والمهني في كل من كندا والولايات المتحدة الأمريكية وأوجه الاستفادة لمصر؟ 6. ما الرؤية المستقبلية لتطوير التعليم الفني والمهني في مصر في ضوء خبرتي كندا والولايات المتحدة الأمريكية؟ منهج الدراسة نظرا لأن طبيعة الدراسة ضمن نطاق الدراسات المقارنة التي تتناول لتطوير التعليم الفني والمهني فإن الباحث يستخدم المنهج المقارن للتعرف على واقع التعليم الفني والمهني في كل من مصر وكندا والولايات المتحدة الأمريكية. خطوات الدراسة سارت الدراسة وفقا لعدد من الخطوات الآتية: الخطوة الأولى: الاتجاهات العالمية المعاصرة لتطوير التعليم الفني والمهني. الخطوة الثانية: وصف واقع التعليم الفني والمهني في مصر في ضوء القوى والعوامل الثقافية المؤثرة فيها. الخطوة الثالثة: وصف واقع التعليم الفني والمهني في كندا في ضوء القوى والعوامل الثقافية المؤثرة فيها. الخطوة الرابعة: وصف واقع التعليم الفني والمهني في الولايات المتحدة الأمريكية ضوء القوى والعوامل الثقافية المؤثرة فيها. الخطوة الخامسة: تحليل مقارن لبيان أوجه التشابه والاختلاف لواقع التعليم الفني والمهني في كل من كندا والولايات المتحدة الأمريكية وأوجه الاستفادة منها في مصر. الخطوة السادسة: رؤية مستقبلية لتطوير التعليم الفني والمهني في مصر في ضوء خبرتي كندا والولايات المتحدة الأمريكية.
This study aims at achieving its objectives by asking a set of questions and answering them. In light of this, the research problem can be formulated in the following questions: The main question: How could technical and vocational education be developed in Egypt in light of the experiences of Canada and the United States of America? The following sub-questions stem from the above question: 1. What are the contemporary global trends for the development of technical and vocational education? 2. What is the reality of technical and vocational education in Egypt in light of the forces and cultural factors affecting them? 3. What is the reality of technical and vocational education in Canada in light of the forces and cultural factors affecting them? 4. What is the reality of technical and vocational education in the United States of America, the light of the forces and the cultural factors that influence them? 5. What is the comparative analysis of the reality of technical and vocational education in Canada and the United States of America and how to benefit from them in Egypt? 6. What is the futuristic vision for the development of technical and vocational education in Egypt in the light of the experiences of Canada and the United States of America? Methodology of the Study Due to the fact that the nature of the study is within the scope of comparative studies dealing with the development of technical and vocational education, therefore the researcher uses the comparative method to identify the reality of technical and vocational education in Egypt, Canada and the United States of America. Study Procedures The study went through a number of steps as follows: The first step: contemporary global trends for the development of technical and vocational education. The second step: description of the reality of technical and vocational education in Egypt in light of the forces and cultural factors affecting them. The third step: description of the reality of technical and vocational education in Canada in light of the forces and cultural factors affecting them. The fourth step: description of the reality of technical and vocational education in the United States of America the light of the forces and cultural factors affecting them. The fifth step: a comparative analysis to show the similarities and differences in the reality of technical and vocational education in Canada and the United States of America and how to benefit from them in Egypt. The sixth step: a futuristic vision for the development of technical and vocational education in Egypt in the light of the experiences of Canada and the United States of America.
Keywords: مصر -- التعليم الفني -- التعليم المهني -- سوق العمل -- الولايات المتحدة الأمريكية -- كندا